Beginning Apache Spark 2 : with resilient distributed datasets, Spark SQL, structured streaming and Spark Machine Learning library /: with resilient distributed datasets, Spark SQL, structured streaming and Spark Machine Learning library. ([2018]) - Luu, Hien
No abstract available